Rituximab, used alone or in combination, is superior to other treatment modalities in splenic marginal zone lymphoma - Else, Monica; Marín-Niebla, Ana; de la Cruz, Fátima; Batty, Paul; Ríos, Eduardo; Dearden, Claire E.; Catovsky, Daniel; Matutes, Estella (British journal of haematology, 2012)
Summary Splenic marginal zone lymphoma (SMZL) is a rare B‐cell malignancy, with no standard treatment other than splenectomy. Rituximab has shown encouraging results. We therefore retrospectively assessed 43 patients from two centres, who received rituximab, either alone or with chemotherapy. All patients responded, 34/43 (79%) achieving a complete response (CR), compared with 3/10 (30%) after chemotherapy without rituximab (P = 0·005). Of these 10 patients, 9 (90%) subsequently achieved a CR after rituximab (P = 0·02). Rituximab monotherapy appeared equally as effective as rituximab combination therapy (90% vs. 79% CR, P = 0·7) with significantly less toxicity (12·5% vs. 83%, P = 0·002). Splenectomized patients were more likely to obtain a CR with rituximab (16/16, 100%) than unsplenectomized patients (18/27, 67%, P = 0·008). Disease‐free survival (DFS) at 3 years was better after rituximab than after splenectomy alone [79% (95% confidence interval 60–89) vs. 29% (8–54), Hazard ratio (HR) 0·28 (0·12–0·68), P = 0·003] and better than after chemotherapy without rituximab [25% (4–55), HR 0·21 (0·08–0·51), P = 0·0004]. Survival at 3 years after rituximab was 98%. In summary, the CR and DFS rates after rituximab, given alone or with chemotherapy, were significantly better than after chemotherapy without rituximab in the same patients, with manageable toxicity. Rituximab, with or without splenectomy, should be considered for the treatment of SMZL.